Perceived facilitators and barriers against human papillomavirus vaccine among rural parents with eligible daughters in the Alle district, Southern Ethiopia - Selemaye Zenebe; Tomas Yeheyis; Fikru Tadesse; Bedilu Deribe; Gezhagn Geresu; Tsehaynew Kasse; Susanne Unverzagt; Eric Sven Kroeber; Eva Johanna Kantelhardt; Lesley Taylor; Betty Ferrell (PLoS ONE, 2026)
Introduction Human papillomavirus vaccine acceptance is influenced by the parental perceptions of the vaccine, but there are few related studies in Ethiopia, and most have focused on quantitative approaches. Therefore, this qualitative study intended to explore parental perceptions about the human papillomavirus vaccine acceptance. Objective To explore the perceived facilitators and barriers against human papillomavirus among rural parents with eligible daughters in the Alle district, southern Ethiopia. Methods A qualitative study using focus group discussion and in-depth interviews was conducted from April 25, 2023, to May 25, 2023, among eligible parents of daughters in the Alle district, southern Ethiopia. A convenience sample of 53 parents was recruited for focus group discussions, and 15 parents were purposely sampled for in-depth interviews. The data were collected by a semi-structured focus group discussion guide and in-depth interview questionnaires. The interview data were translated into English after transcription, and thematic analysis was done by Atlas software version 7.1.16. Results Among the total participants, 66.2% were female parents and 60.2% were protestant religious followers. Findings were split between two major themes: perceived facilitators and barriers to human papillomavirus vaccine acceptance. The perceived facilitators identified were preventing cervical cancer, seeing it as an expression of parental role and responsibility, and believing in the recommendation of health professionals as facilitators of human papillomavirus vaccination. The identified perceived barriers to human papillomavirus vaccination included: a lack of awareness, a lack of reliable information sources, a lack of trust in the vaccine, misconceptions, fear of side effects, and cultural and religious factors affecting the acceptance of human papillomavirus vaccination. Conclusion Parents identified various facilitators and barriers to accepting the human papillomavirus vaccine. Therefore, we recommend that the government and concerned institutions work in collaboration to address the identified challenges to improve the acceptance of human papillomavirus vaccination.